2016
DOI: 10.1007/s00436-016-5000-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medicated feeds with antiparasitical and immune-enhanced Chinese herbal medicines against Ichthyophthirius multifiliis in grass carp (Ctenopharyngodon idellus)

Abstract: Since malachite green was banned for using in food fish due to its carcinogenic and teratogenic effects on human, the search of alternative drug to treat Ichthyophthirius multifiliis becomes urgent. This study aimed to (1) evaluate the ethanol extracts of medicinal plants Cynanchum atratum, Zingiber officinale, Cynanchum paniculatum, immunostimulant (A), and immunostimulant (B) for their efficacy against I. multifiliis, and (2) determine effects of medicated feeds with C. atratum, Z. officinale, C. paniculatum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…A concentration of 8 mg/L for Z. officinale was 100 % effective against theronts and a concentration of 4 mg/L of C. atratum was sufficient to kill encysted tomonts. Applying the extract to the feed had a limited effect [109]. Another study showed that cynatratoside-C isolated from C. atratum showed 100 % mortality against I. multifiliis theronts from grass carp in approximately three hours at a low concentration of 0.25 mg/L.…”
Section: Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…A concentration of 8 mg/L for Z. officinale was 100 % effective against theronts and a concentration of 4 mg/L of C. atratum was sufficient to kill encysted tomonts. Applying the extract to the feed had a limited effect [109]. Another study showed that cynatratoside-C isolated from C. atratum showed 100 % mortality against I. multifiliis theronts from grass carp in approximately three hours at a low concentration of 0.25 mg/L.…”
Section: Plant Extractsmentioning
confidence: 99%
“…Zingiber officinale Ethanol extract Grass carp -4 % (feed, days) 0/0 51.6 (significant) [109] Cynanchum atratum Ethanol extract Grass carp -4 % (feed, 10 days) 0/0 76.5 (significant) [109] Cynatratoside Contr. = control 495…”
Section: Biological Control Strategiesmentioning
confidence: 99%
“…In comparison, it took 4 h to kill all theronts using commercially available copper naphthenate at a concentration of 8 mg/L (organic copper content = 2.4%) [ 27 ]. The concentrations of ethanol extracts of Zingiber officinale and Cynanchum atratum needed to achieve 100% theronts mortality were 8 mg/L and 16.0 mg/L, respectively [ 28 ]. The concentration of berberine needed to achieve 100% theront mortality at the 4 h time point was much lower than that of garlic extract, which required 62.5 mg/L for 15 h [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These oxidizing agents are being applied in increasing amounts, but the search for alternative products is still ongoing. Herbal extracts have exhibited strong effects on different stages of the parasite (Lin et al , 2016; Mathiessen et al , 2021a), but before licensing, marketing and possible application at farm level, further investigations into the environmental impact, toxicity towards the host and any effect on human health are needed. Correspondingly, a lipopeptide (surfactant) isolated from the bacterium Pseudomonas H6 has lethal effects on the theronts, tomonts and tomocysts of Ichthyophthirius (Al-Jubury et al , 2018; Li et al , 2022).…”
Section: Parasites In Aquaculturementioning
confidence: 99%